2006
DOI: 10.1116/1.2181580
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the spatial distribution and molecular weight of polymethylmethacrylate fragments in electron beam lithography exposures

Abstract: We report a three-dimensional (3D) simulation model based on the kinetic transport theory for calculating the distribution of PMMA fragments after an exposure to electron impact. The conditions employed for the modeling were chosen to resemble a typical electron beam lithography exposure. The model accounts for inelastic collisions of electrons in PMMA and resulting random main-chain scissions. We have considered gratings composed of parallel lines distanced by 10–50nm and exposed to electrons with energies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
0
48
0
3
Order By: Relevance
“…Use of such empirical Gfactors involves a significant level of uncertainty, since the experimental conditions differ dramatically from those employed in EBL. We have also shown that the G-factor is not necessarily a constant, but may depend on the energies of electrons involved in collisions (Aktary et al, 2006), which should be accounted for. Furthermore, using the distributions of deposited energy as a starting point for the computations of the number of scissions is not an unequivocal choice, since a part of deposited energy is thermalized without scissions involved, whereas the actual yield of scissions is related intimately with the details of individual collisions of electrons with atoms of PMMA.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations
“…Use of such empirical Gfactors involves a significant level of uncertainty, since the experimental conditions differ dramatically from those employed in EBL. We have also shown that the G-factor is not necessarily a constant, but may depend on the energies of electrons involved in collisions (Aktary et al, 2006), which should be accounted for. Furthermore, using the distributions of deposited energy as a starting point for the computations of the number of scissions is not an unequivocal choice, since a part of deposited energy is thermalized without scissions involved, whereas the actual yield of scissions is related intimately with the details of individual collisions of electrons with atoms of PMMA.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Outline of our model for resist exposure in EBL. In the model, the probability of main-chain scissions is computed directly through the differential cross-section for inelastic collisions resulting in the scissions (Aktary et al, 2006). The model avoids uncertainties related with the conversion of the distributions of deposited energy into the number of main-chain scissions through the empirical radiation chemical yield.…”
Section: Towards New Modeling Paradigm For Exposures Of Positive Resistsmentioning
confidence: 99%
See 1 more Smart Citation
“…PMMA ͑polymethylmethacrylate͒ is an important polymer because of its wide use as an electron resist for high resolution lithography [14][15][16][17][18][19] for forming patterns for microand nanodevices. Gold has been used as a dopant metal species for PMMA doping but not by using ion implantation as the doping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the work described here we have used very low energy gold ion implantation into thin films of polymethylmethacrylate ͑PMMA͒. PMMA is an important polymer used widely as a resist for high resolution lithography by electron beam, [15][16][17][18][19][20][21][22] ion beam, deep-UV, and x-ray irradiation. 21,22 For the extremely low ion energy used here, the buried conducting layer is only a few nanometers deep and of width about 1 nm.…”
mentioning
confidence: 99%